AVOID EXCESSIVE EXPOSURE TO THE HOT WEATHER - MPRC, Pusat Media & Perhubungan Awam (USM, 2016)
USM, PENANG, 25 March 2016 – The public needs to give serious attention to the heat wave that is hitting the country now.